Estimated IQ points and lifetime earnings lost to early childhood blood lead levels in the United States - Boyle, Joseph; Yeter, Deniz; Aschner, Michael; Wheeler, David C. (The Science of the total environment, 2021)
There is no safe detectable level of lead (Pb) in the blood of children. Blood lead levels (BLLs) at ages 6–24 months ≥2 μg/dL result in lost grade school intelligence quotient (IQ) points at ages 5–10 years. Black children continue to have the highest BLLs in the United States. Therefore, we examined currently undetermined racial/ethnic disparities in anticipated IQ points and associated lifetime earnings lost to early childhood blood lead. We conducted secondary analysis of infants with blood lead (in μg/dL) measured at ages 12–24 months by the cross-sectional National Health and Nutrition Examination Survey (NHANES) during 1999 to 2010. Nationally-representative estimates were produced using weighted simulation model. A total of 1241 infants were included from the NHANES sample (52% male; mean [SD] age, 18.5 [3.5] months; 25% Black [non-Hispanic], 42% Hispanic [any race], 5% Other/Multiracial, and 29% White [non-Hispanic]) after excluding 811 without BLL determinations. For national outcomes, Black infants experienced approximately 46–55% greater average estimated loss of grade school IQ points from blood lead than Hispanic or White infants (−1.78 IQ points vs. –1.15 and −1.21 respectively) with similar disparities in costs to expected lifetime earnings (−$47,116 USD vs. −$30,393 and −$32,356 respectively). Our estimated nationwide costs of IQ points lost to BLLs during this 12-year period totaled $554 billion ($46.2 billion/year), in which blood lead <5 μg/dL accounted for 74% of this total burden. We report two aspects of the substantial national costs attributable to lead exposure in just the second year of life alone, which disproportionately impact predominately African-American Black infants from continuing legacies of environmental racism in lead exposure. Our findings underscore the remarkably high costs from recognized hazards of blood lead even at the lowest levels and the importance of primary prevention regarding childhood lead exposure. [Display omitted] •Despite decreasing lead levels in the USA, there is no safe level of lead in blood.•We simulated a nationwide sample of infants using cross-sectional survey data.•We estimated IQ points and lifetime earnings lost based on lead levels.•Black infants experienced higher IQ point and earning loss due to blood lead.•Low levels of blood lead explain the majority of estimated lifetime earning loss.